The Shape of Agency Control, Action, Skill, Knowledge - Shepherd, Joshua (Oxford University Press, 2021)
In this book Shepherd offers a perspective on the shape of agency by offering interlinked explanations of the basic building blocks of agency, as well as its exemplary instances. In the book's first part, he offers accounts of phenomena that have long troubled philosophers of action: control over behavior, non-deviant causation, and intentional action. These accounts build on earlier work in the causalist tradition and undermine the claims of many that causalism cannot offer a satisfying account of non-deviant causation, and therefore intentional action. In the book's second part, he turns to modes of agentive excellence-ways that agents display quality of form. He offers a novel account of skill, including an account of the ways that agents display more or less skill. He discusses the role of knowledge in skill and concludes that while knowledge is often important, it is inessential. This leads to a discussion of knowledge of action-of the way that knowledge of action and knowledge of how to act informs action execution. Shepherd argues that knowledgeable action includes a unique epistemic underpinning. For in knowledgeable action, the agent has authoritative knowledge of what she is doing and how she is doing it when and because she is poised to control her action by way of practical reasoning.